Profiles of Early Childhood Education Program and Children Attending Them - Lisa Pangemanan; Mira Irmawati; Irwanto Irwanto; Ahmad Suryawan (Health Notions, 2018)
Early childhood education (ECE) in Indonesia is growing with many variations in programs among the ECE. Children’s profile in those places were varied in terms of growth and development.This research aims to study the profiles in ECE in terms of program’s variation, growth and development of children attend it. This research uses a cross-sectional study was done in 3 ECE centers in Surabaya, which are varied in total effective hours, the use of language, and teacher-student ratio. The growth outcome was assessed by anthropometric measurement. The developmental outcome was assessed using Denver II. Statistical analysis was done by Kruskal-Wallis test. A total of 52 children from three ECE centers were enrolled. Program variations among 3 ECE were as follow: total effective hours per day (3, 2.5 and 3.5), the use of language (1, 1, and 2); and teacher-student ratio (1:7, 1:19, 1:15) respectively. Anthropometric measurements of those ECE were as follow: body weight in kg (16.9 (SD 5.10); 17 (SD 2.46); 17.9 (SD 4.62) (p ≥ 0.05)); body height in cm (100.7 (SD 5.72); 105 (SD 5.89); 104.7 (SD 6.31) (p ≥ 0.05)); head circumference in cm (49.5 (SD 1.75); 50.5 (SD 1.74); 50.6 (SD 1.59) (p ≥ 0.05)) respectively. Suspected developmental delays were 11, 9, 11 children (p ≥ 0.05) respectively. Development problem found was mainly in language and personal social. There are program’s variation among ECE but the growth and development profiles of children attend it were similar. Keywords: Variation, ECE program, Growth, Development